The Role of CD90 in the Differential Diagnosis of Pleural Malignant Mesothelioma, Pulmonary Carcinoma and Comparison with Calretmm - ŞAHİN, NURHAN; Sahin, NURHAN; AKATLI, AYŞE NUR; ÇELİK, MUHAMMET REHA; ULUTAŞ, HAKKI; Samdanci, Emine Turkmen; ÇOLAK, CEMİL (My University, 2017)
Pleural Malignant Mesothelioma (MM) is a fatal disease that has been associated with asbestos exposure. Differential diagnosis between the pleural infiltration of pulmonary carcinomas and MM is rather difficult particularly for epitheloid type mesothelioma. We aimed to investigate the utility of CD90, a cancer stem cell marker, in the differential diagnosis of MM and lung carcinoma, its prognostic significance and compare its value with that of Calretinin. Ninety pathology specimens including MM (n:30), pulmonary adenocarcinoma (n:30) and pulmonary squamous cell carcinoma (n:30) were used in this study. Immunohistochemical comparision of CD 90 and Calretinin was made in all groups. Calretinin was positive in 20 cases with MM (64.5 %), and was negative in 10 (32.3 %). CD 90 was positive in 25 of these cases (80 %) and negative in 5 (16 %). On the other hand pulmonary adenocarcinomas and squamous cell carcinomas showed positivity with CD90, 63,6 % and 73 %, respectively. We think that CD 90 has no place in the differential diagnosis between mesothelioma and pulmonary carcinoma because of the low specificity in spite of the high sensitivity.